Buyer Credit Pricing for Natural Gas Exports Using Country Risk Ratings - Simpson, John (Springer-Verlag Berlin Heidelberg, 2013)
It is important for exporters of commodities, including natural gas, to price their exports correctly in times of excess demand. It is equally important for providers of buyer credit for importers of natural gas to price the finance for the shipments correctly. Pricing buyer credit is vital for the lender’s goals, which includes shareholder wealth maximization if the lender is a bank or a corporation, but, more importantly pricing credit is important for the optimization of the risk and return relationship and the diversification of unsystematic risks in export loan assets. In this chapter, the price of natural gas from a gas exporting country, such as Australia, is deemed to be the amount of export finance that might be required as buyer credit. Export returns thus represent the change in the amount of export finance required by buyers. A higher buyer credit change means a greater amount of credit required. Using country risk ratings, a risk premium is ascribed to this buyer credit in order to avoid mispricing of exports and buyer credit in times of excess demand for gas and thus buyer credit. Importer country examples of the US and China are investigated. It is posited that country risk ratings can determine the magnitude of the risk premium to be applied to buyer credit, consistent with risk/return trade-off theory.